2023
DOI: 10.3389/fped.2023.1130790
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional impact of CFTR modulators in children with cystic fibrosis

Abstract: BackgroundNutritional status is a major prognostic factor for breathing and the survival of patients with cystic fibrosis (CF). Since 2012, the development of CFTR modulators has considerably transformed the outcome of this disease. Indeed, both lung function and body mass index are improved by CFTR modulators, such as Lumacaftor/Ivacaftor. However, few data exist regarding the outcome of nutritional intakes under Lumacaftor/Ivacaftor.MethodsWe conducted a prospective single-center study in children with CF tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…An increase in BMI in both children and adults has been noted in many studies after the initiation of modulator therapies, with greater weight gain after highly effective modulator therapies such as Iva (for PwCF with gating mutations) and ETI 21,22,28‐36 . Petersen and colleagues found that the mean rate of change in BMI was 1.47 kg/m 2 /yr (95% confidence interval, 1.08–1.87) greater after initiation of ETI.…”
Section: Discussionmentioning
confidence: 98%
“…An increase in BMI in both children and adults has been noted in many studies after the initiation of modulator therapies, with greater weight gain after highly effective modulator therapies such as Iva (for PwCF with gating mutations) and ETI 21,22,28‐36 . Petersen and colleagues found that the mean rate of change in BMI was 1.47 kg/m 2 /yr (95% confidence interval, 1.08–1.87) greater after initiation of ETI.…”
Section: Discussionmentioning
confidence: 98%
“…Other reasons might include changes in intestinal pH, intestinal absorption of bile salts or changes in intestinal transit time [ 46 ]. Gaschignard et al reported significantly increased Vitamin E levels 10 months after therapy with luma-/ivacaftor and Gelzo et al reported higher vitamin E levels after luma-/ivacaftor therapy as well [ 21 , 30 ]. Sommerburg et al on the contrary reported a moderate but significant decrease in vitamin E and vitamin E/cholesterol one and two years after luma-/ivacaftor [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sommerburg et al on the contrary reported a moderate but significant decrease in vitamin E and vitamin E/cholesterol one and two years after luma-/ivacaftor [ 22 ]. Vitamin A and D levels also rose, not-significantly in one study [ 30 ] but another report shows increased vitamin A levels [ 22 ]. Similar results have been published for ETI therapy: Both vitamins A and D levels increased in an adult cohort and vitamin A increased in a pediatric cohort [ 28 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations